Cyclohexane, a Potential Drug of Abuse with Pernicious Effects on the Brain - Campos-Ordonez, Tania; Gonzalez-Perez, Oscar (Frontiers in Pharmacology, 2016)
Cyclohexane is a volatile solvent used as a harmless substitute for dangerous organic solvents in several products, such as paint thinners, gasoline and adhesives. Many of these products are used as drugs of abuse and can severely damage neural tissue and impair neurological functions. However, there is very little information on the effects of cyclohexane on the brain. In humans, cyclohexane produces headaches, sleepiness, dizziness, limb weakness, motor changes and verbal memory impairment. Recent studies in mice have demonstrated behavioral alterations, reactive gliosis, microglial reactivity and oxidative stress in the brains of cyclohexane-exposed animals. This indicates that cyclohexane may represent a potential problem for public health. Therefore, studies are needed to clarify the neurobiological effects of this volatile compound, including the cellular and molecular mechanisms of neurotoxicity, and to minimize the human health risk posed by the intentional or accidental inhalation of this potential drug of abuse.